Rancang Bangun Chatbot QA dengan Framework Flowise AI untuk Layanan Informasi Penerimaan Mahasiswa Baru (Studi Kasus : Universitas Prabumulih) - ZB, Yuntari Purbasari; Setiawan, Iwan; Suhartini, Suhartini (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2025)
The development of Artificial Intelligence (AI) technology has had a significant impact across various sectors, including higher education. One promising AI implementation is a Question Answering (QA)-based chatbot to assist in delivering information automatically and efficiently. This study aims to design and develop a QA chatbot using the Flowise AI framework as an information service solution for new student admissions at Universitas Prabumulih. The system development method includes requirements analysis, chatbot architecture design, implementation with integration of a Large Language Model (LLM), and functionality testing. The testing results show that the chatbot is capable of providing relevant and prompt answers to various frequently asked questions related to student admissions, such as registration requirements, selection schedules, and tuition fees. The implementation of this chatbot is expected to improve the quality of information services and communication efficiency between prospective students and the university.